A Highly Stable Bimetallic Transition Metal Phosphide Catalyst for Selective Dehydrogenation of n-Heptane - Stöber, Robert; Mai, Florian; Oshin, Oshin; Körner, Andreas; Hutzler, Andreas; Schühle, Patrick (ChemCatChem, 2022)
In this work, we demonstrate RuP2-MoP catalysts being highly stable and selective for the dehydrogenation of long-chain alkanes like n-heptane. Compared to a monometallic MoP catalyst, the bimetallic system substantially increases n-heptene selectivity from 40 % towards 80 %. This effect can be traced back to a reduced surface acidity, suppressing the competitive hydrogenolysis reaction. The active transition metal phosphide is, furthermore, compared to its phosphorous-free RuMo-counterpart. As revealed by STEM-EDX investigations, incorporation of phosphorous results in the formation of separated metal phosphide clusters instead of an intermetallic alloy. In the dehydrogenation of n-heptane the phosphorous modification clearly avoids catalyst deactivation and maintains the high n-heptene selectivity. X-ray diffraction, elemental analysis and STEM-EDX further reveal that catalyst coking and the formation of less active molybdenum carbide phases is effectively suppressed by phosphorous incorporation, making RuP2-MoP an attractive system for selective dehydrogenation of long-chain alkanes.
CRIS-Team Scopus Importer:2022-08-12
Keywords: Alkane dehydrogenation; Coking resistance; Heterogeneous catalysis; Molybdenum catalyst; Transition metal phosphides

Ga-Pt supported catalytically active liquid metal solutions (SCALMS) prepared by ultrasonication - influence of synthesis conditions on n-heptane dehydrogenation performance - Oshin, Oshin; Al-Shaibani, Asem; Taccardi, Nicola; Sultan, Umair; Inayat, Alexandra; Vogel, Nicolas; Haumann, Marco; Wasserscheid, Peter (Catalysis: Science and Technology, 2023)
Supported catalytically active liquid metal solution (SCALMS) materials represent a recently developed class of heterogeneous catalysts, where the catalytic reaction takes place at the highly dynamic interface of supported liquid alloys. Ga nuggets were dispersed into nano-droplets in propan-2-ol using ultrasonication followed by the addition of Pt in a galvanic displacement reaction - either directly into the Ga/propan-2-ol dispersion (in situ) or consecutively onto the supported Ga droplets (ex situ). The in situ galvanic displacement reaction between Ga and Pt was studied in three different reaction media, namely propan-2-ol, water, and 20 vol% water containing propan-2-ol. TEM investigations reveal that the Ga-Pt reaction in propan-2-ol resulted in the formation of Pt aggregates on top of Ga nano-droplets. In the water/propan-2-ol mixture, the desired incorporation of Pt into the Ga matrix was achieved. The ex situ prepared Ga-Pt SCALMS were tested in n-heptane dehydrogenation. Ga-Pt SCALMS synthesized in pure alcoholic solution showed equal dehydrogenation and cracking activity. Ga-Pt SCALMS prepared in pure water, in contrast, showed mainly cracking activity due to oxidation of Ga droplets. The Ga-Pt SCALMS material prepared in water/propan-2-ol resulted in high activity, n-heptene selectivity of 63%, and only low cracking tendency. This can be attributed to the supported liquid Ga-Pt alloy where Pt atoms are present in the liquid Ga matrix at the highly dynamic catalytic interfac
Keywords: Binary alloys; Dehydrogenation; Drops; Heptane; Liquid metals; Platinum alloys; Substitution reactions; Cracking activity; Ex situ; Galvanic displacement reactions; matrix; Metal solutions; n-Heptanes; Nano-droplets; Performance; Synthesis conditions; Ultra-sonication; Catalysis

Kinetics of dehydrogenation of n-heptane over GaPt supported catalytically active liquid metal solutions (SCALMS) - Oshin, Oshin; Al-Shaibani, Asem; Taccardi, Nicola; Haumann, Marco; Wasserscheid, Peter (Reaction Chemistry & Engineering, 2024)
The concept of Supported Catalytically Active Liquid Metal Solutions (SCALMS) was explored for the catalytic dehydrogenation of n-heptane. For this purpose, a GaPt on alumina (Ga84Pt/Al2O3) was compared with a Pt on alumina catalyst at different reaction temperatures and feed compositions. While the observed activation energies with both catalysts for the overall n-heptane depletion rate were similar with both catalysts, the SCALMS systems provides a lower activation energy for the desired dehydrogenation path and significantly higher activation energies for the undesired aromatization and cracking reaction. Thus, the SCALMS catalyst under investigation shows technically interesting features, in particular at high temperature operation. The partial pressure variation revealed an effective reaction order of around 0.7 for n-heptane for both catalysts, while the effective order for hydrogen was 0.35 for Pt/Al2O3 and almost zero for SCALMS.
CRIS-Team Scopus Importer:2024-02-16

Stable and Selective Dehydrogenation of Methylcyclohexane using Supported Catalytically Active Liquid Metal Solutions – Ga52Pt/SiO2 SCALMS - Oshin, Oshin; Nair, Sharanya Sukumar; Taccardi, Nicola; Wolf, Moritz; Soegaard, Alexander; Haumann, Marco; Wasserscheid, Peter (ChemCatChem, 2020)
The use of gallium-rich, Supported Catalytically Active Liquid Metal Solution (SCALMS) is a promising new concept to achieve catalysis with atomically dispersed active metal atoms. Expanding our previous work on short alkane dehydrogenation, we present here the application of SCALMS for the dehydrogenation of methylcyclohexane (MCH) to toluene (TOL) using a Ga52Pt alloy (liquid under reaction conditions) supported on silica. Cycloalkane dehydrogenation catalysis has attracted great attention recently in the context of hydrogen storage concepts using liquid organic hydrogen carrier (LOHC) systems. The system under investigation showed high activity and stable conversion of MCH at 450 °C and atmospheric pressure for more than 75 h time-on-stream (XMCH=15 %) with stable toluene selectivity (STOL) of 85 %. Compared to commercially available Pt/SiO2, the SCALMS system resulted in higher yields and robustness. Baseline experiments with Pt-free Ga/SiO2 under identical conditions revealed the decisive influence of Pt dissolved in the liquid Ga matrix.
CRIS-Team Scopus Importer:2020-08-14
Keywords: Alloys; dehydrogenation; gallium; methylcyclohexane; platinum; supported catalysts